Shoot induction on several cutting types of corm of shrimp banana (Musa acuminata Colla) through in vitro culture - Mayta Novaliza Isda; Elvianis Elvianis; Siti Fatonah (Universitas Andalas, 2020)
Musa acuminata Colla is a unique genomic species which differs from other species in this genus. It has typical color of reddish-purple on its fruit. Musa acuminata is recorded as rare banana in Riau, particularly in Kampar District. This research aims to study the influence of several cutting types of corm of shrimp banana originated from Kampar District through in vitro culture. It also purposes to determine the best formation of M. acuminata shoot through various concentration treatments of BAP only and BAP combined with Kinetin. The study used randomized block design (RBD) by adding come BAP concentration (0, 4, 8 mg/l) and BAP combined with Kinetin (0 mg/l BAP+0.4 mg/l Kinetin, 4 mg/l BAP+0.4 mg/l Kinetin, and 8 mg/l BAP+ 0.4 mg/l Kinetin). The cutting type of banana corm involve no cut (whole) and half-to-half cutting in MS media, each with 5 replicates. The result showed that either addition of BAP and BAP combined with Kinetin gave the best percentage of live explants and shot formation up to 100%. Treatment of 8 mg/l BAP resulted in the highest shoot percentage up to 100%, the fastest shoots appearance at 34.00 days after planting and the longest shoot reached 2.83 cm with 2.33 shoots counted on half-to-half cutting type. This study also confirmed that the addition of plant regulation substances from cytokinin group gave good impact in the formation of shrimp banana shoots.